Patient and Parent Satisfaction With Sling Use After Pediatric Upper Extremity Fractures: A Randomized Controlled Trial of a Customized Cast-Sling Versus Standard Cast and Sling. Issue 2 (February 2019) - Cruz, Aristides I.; DeFroda, Steven F.; Gil, Joseph A.; Hansen, Heather; Bolous, Alexandre; Procaccini, Michaela; Zonfrillo, Mark R.
Abstract : Background: Long arm cast immobilization after operative and nonoperative treatment of pediatric upper extremity fractures is common. The use of a sling to aid in carrying the casted extremity as well as provide further immobilization is also common practice. Off-the-shelf slings vary in quality and fit, can be confusing for parents/patients to apply, and lead to frustration and dissatisfaction with its use. The purpose of this investigation was to compare patient/parent centered outcomes after the use of a customized sling compared with a standard sling by utilizing a prospective, randomized-controlled trial. We hypothesized that patients and their parents would find the "Providence" Pedi Cast-Sling (PPCS) to be more convenient and be more satisfied with its use compare with a standard sling. Methods: Eligible subjects included patients 0 to 18 years old, evaluated at an urban, tertiary care pediatric emergency department (ED), who sustained an upper extremity fracture that required placement of a long-arm cast. Exclusion criteria were: open fractures; fractures at multiple levels; fractures requiring urgent/emergent surgery; admitted patients; bivalved casts. Patients were randomized to receive a standard sling or a PPCS. Questionnaires assessing patient/parent satisfaction, preferences, sling-use, and pain level were collected at patients' first follow-up visit. Results: A total of 100 patients were randomized with 71 questionnaires available for analysis (39 standard sling vs. 32 PPCS). There were statistically significant differences for satisfaction scores for all related questions between patients who received a PPCS compared with a standard sling. Patients and their parents were more likely to choose the PPCS ( P =0.001), were more satisfied with the PPCS ( P <0.006), and reported the PPCS to be more convenient than a standard sling ( P <0.001). P atients who received a PPCS wore the sling for a greater number of hours during the day (10.3±7.1 h) compared with those who received a standard sling (5.9±5.0 h) ( P =0.004). Conclusions: The "Providence" Pedi Cast-Sling is a superior alternative to an off-the-shelf sling when used after the application of a long-arm cast providing greater convenience, compliance, and satisfaction to both patients and families. Level of Evidence: Level I—Prospective randomized-controlled trial.